KONSTRUKSI EKONOMI POLITIK MEDIA MASSA: KASUS PEMBERITAAN ILLEGAL LOGGING PADA PT. RAPP (2009-2010) - Albintani, Muchid (Universitas Riau, 2012)
PT. Riau Andalan Pulp and Paper (RAPP) and the activities of Illegal Logging inthe period 2009-2010 the focus of mass media. The focus of the reports motivatedby contradictory realities. On the one hand for the first time since a RegionalHead of local autonomy (Regent) was convicted of corruption (graft) relatedlicense for utilization of timber forest products (IUPHHK) that led to the illegallogging activities that also involve PT. RAPP. While on the other hand, theMinistry of Forestry by SK MENHUT/327/2009, provides expansion of theSemenanjung Kampar to PT. RAPP considered problematic and potentially theactivity of Illegal Logging. This paper aims to, first analyze the media coverage ofIllegal Logging on the existence PT. RAPP in 2009-2010. Second, describe andanalyze the implications of the media coverage of Illegal Logging on the existencePT. RAPP in 2009-2010. This paper uses constructionist (media) and politicaleconomy communication as a theoretical approach. The results of the discussionshowed that, the first the relationship of Illegal Logging and PT. RAPP has beenconstructed by the media that shows if the presence of both (PT RAPP and IllegalLogging) in the year 2009-2010 run separately and not linked. The second, so thenews about the activities undertaken Illegal Logging ('alleged') in PT RAPP anissue of 'ambiguous' and different from each other. In this context, if the newsshowed Illegal Logging, rather than an integral part of the production process(activities) PT. RAPP.Keywords: PT. RAPP, Illegal Logging and Economics Political Communication